(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic caused significant impacts on the labor market, boosting new arrangements and heavily affecting relationships with the work itself and among employees. Aspects related to working conditions, established links, structure and functioning of organizations and the social function of employment were strongly affected. Therefore, the aim of this article is to understand the impacts of teleworking on workers’ mental health. To achieve this purpose, a bibliographic search was carried out based on scientific references approaching this theme. The results indicate both advantages and disadvantages of teleworking for the organizations and employees. However, we believe that a primary focus of organizations should be directed towards the management of the effects of these new work arrangements to improve health and promote quality of life and well-being for workers.